Complete Genome Sequence of Serratia marcescens WW4 - Chung, Wan-Chia (American Society for Microbiology, 2013)
Serratia marcescens WW4 is a biofilm-forming bacterium isolated from paper machine aggregates. Under conditions of phosphate limitation, this bacterium exhibits intergeneric inhibition of Pseudomonas aeruginosa. Here, the complete genome sequence of S. marcescens WW4, which consists of one circular chromosome (5,241,455 bp) and one plasmid (pSmWW4; 3,248 bp), was determined.